Utilization of BIM Technology, Autocad Software, and Sketch Up in Architectural Design Drawings - Ulinata Ulinata (Publikasi Indonesia, 2024)
Architecture is a science that studies designing a building by applying 3 principles, namely strength, function, and beauty. A building generally consists of a form or pattern in the form of 2 dimensions, for example, the floor plane, the ceiling plane, and others, and the shape/form consists of the shape/shape of a volume (3 dimensions), for example, the space in the building. In designing a building, an architect who is an expert in the field of architecture is needed. This study uses a descriptive method to find out how to make design drawing documents by utilizing BIM technology, AutoCAD software, and SketchUp. The results show that BIM technology, AutoCAD software, and Sketch can produce architectural design drawings more efficiently in terms of time, and cost and produce more accurate image quality. From the explanation above, it can be concluded that the results show that the use of BIM technology, AutoCAD software, and sketch-up in architectural design can produce architectural design drawings more efficiently in terms of time, and cost and produce more accurate image quality.